Wormlike Perovskite Oxide Coupled with Phase‐Change Material for All‐Weather Solar Evaporation and Thermal Storage Applications. Issue 3 (15th January 2023) - Irshad, Muhammad Sultan; Arshad, Naila; Zhang, Jian; Song, Changyuan; Mushtaq, Naveed; Alomar, Muneerah; Shamim, Tariq; Dao, Van-Duong; Wang, Hao; Wang, Xianbao; Zhang, Han
Abstract : Interfacial solar‐driven water evaporation has shown promising prospects in desalination technology. However, the lower photothermal conversion efficiency caused by the intermittent nature of sunlight and salt accumulation remains a significant challenge for continuous desalination. Herein, the hierarchical design of interfacial solar evaporation is reported, which realizes enhanced photothermal conversion, waste heat storage/release, and effective thermal management for continuous desalination. The solar evaporator is composed of worm‐like SrCoO3 perovskite oxide anchored on super hydrophilic polyurethane (PU) foam succeeded by in situ polymerization of conducting polypyrrole (SrCoO3 @PPy). The energy storage system is introduced within polyurethane matrix by a paraffin block followed by a tongue‐and‐groove structure for convective water transportation, and a heat recovery unit largely reduces heat losses. The solar evaporator possesses excellent evaporation rates (2.13 kg m −2  h −1 ) along with 93% solar‐to‐vapor conversion efficiency under 1 kw m −2 solar irradiation owing to its minimum equivalent evaporation enthalpy and (0.85 kg m −2  h −1 ) under intermittent solar irradiation as compared to conventional solar evaporators. More importantly, state‐of‐the‐art experimental investigations validate waste heat recovery/release and the salt‐resistant capability of solar evaporators optimized by computational fluid dynamic simulation. This study breaks conventional solar interfacial evaporation's limitations and demonstrates stable desalination under intermittent sunlight. Abstract : The all‐weather solar‐driven evaporation system realizes enhanced evaporation rate (2.13 kg m −2  h −1 ) with 93% solar‐to‐vapor conversion efficiency under 1 kw m −2 solar irradiation owing to its minimum equivalent evaporation enthalpy. A self‐regeneration and thermal storage system for continuous desalination is realized without any salt accumulation or surface fouling under intermittent solar irradiation.